Comparación de la comprensión lectora en alumnos de cuarto año de secundaria de centros educativos estatales y no estatales de Lima Metropolitana - Delgado V., Ana (2014)
Objectives: a. To study the reading comprehension development on fourth grade high school students. b. To analyze the comprehension developmental level of fourth grade high school students considering public and private schools. c. To compare the reading comprehension level considering student’s gender on fourth grade high school students. d. To study the psychometric properties of the research instrument. e. To study the reading comprehension construct using the confirmatory factorial analysis. Design: Descriptiv.comparative study carried on fourth grade high school students of public and private schools considering students gender. Materials and methods: A b.etapic conglomerate sampling affixed to size, the participants were 613 students of seven units (UGEL) of Lima city. It was constructed a reading comprehension test for fourth level high school students. The statistical analysis considered three stages: Psychometric study in order to calculate validity and reliability index, descriptive indicators, and inferential hypothesis testing. Results: 64,77% fourth grade high school students were from public schools while 35,23% were from private schools. 46,33% fourth grade high school students were male while 53.67% were female. Conclusions: It has been found that the instrument is valid and reliable. It was found statistically differences on reading comprehension level considering public and private schools (higher on these ones). The fourth grade high school students of private schools have more reading comprehension on literal and inferential reading. However there were no differences between male and female students. Norms have been constructed for each kind of school.